Performance evaluation of micro - irrigation devices - JACOB BIJO DANIEL; Er. Vishnu B (Guide) (Tavanur 2003 Department of Land and Water Resources and Conservation Engineering)
Performance evaluation of micro - irrigation devices
Performance evaluation of micro - irrigation devices